2019
DOI: 10.1039/c9nr07236e
|View full text |Cite
|
Sign up to set email alerts
|

Ambient oxidation of Ti3C2 MXene initialized by atomic defects

Abstract: The mechanism of Ti3C2-MXene ambient oxidation has been revealed by electron microscopy, disclosing the effects of defects and Ti-ion diffusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
172
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(178 citation statements)
references
References 33 publications
6
172
0
Order By: Relevance
“…Xia et al [52] reported the oxidation of Ti 3 C 2 T x MXene under ambient conditions (room temperature), where dispersions of synthesized MXenes were stored in tin (Sn)wrapped vials to neglect the probability of light-induced oxidation. Further, the mechanism behind the oxidation of MXene (Ti-based, Ti 3 C 2 T x ) was explored.…”
Section: Oxidative Degradation Of Mxenes and Influencing Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Xia et al [52] reported the oxidation of Ti 3 C 2 T x MXene under ambient conditions (room temperature), where dispersions of synthesized MXenes were stored in tin (Sn)wrapped vials to neglect the probability of light-induced oxidation. Further, the mechanism behind the oxidation of MXene (Ti-based, Ti 3 C 2 T x ) was explored.…”
Section: Oxidative Degradation Of Mxenes and Influencing Parametersmentioning
confidence: 99%
“…Ti atoms in the MXene layers are oxidized to form TiO 2 nanoparticles, whereas C atoms in the MXene layers agglomerate and develop an amorphous carbon structure. The formation of TiO 2 nanocrystals and amorphous carbon is explained by the following equation [52]:…”
Section: Oxidative Degradation Of Mxenes and Influencing Parametersmentioning
confidence: 99%
“…[ 21,27 ] Other aspects may also contribute to the oxidation of MXenes, such as the amount and types of terminal groups, etching conditions, ultraviolet exposure, and the number of defects on the MXene nanosheets. [ 3,28,29 ]…”
Section: Introductionmentioning
confidence: 99%
“…demonstrated the mechanism of ambient degradation of Ti 3 C 2 MXene where titanium oxide starts to grow in the vicinity of basal and edge atomic defects. [ 109 ] Positively charged titanium vacancies induce the formation of amorphous carbon, while oxidation of Ti cations and the following formation of TiO 2 occur at nearby positions. At the same time, Nb adatoms at the Nb 2 CT x MXene surface contact with ambient O, forming oxide nanoclusters that start to destroy local structural order with following degradation of the entire MXene sheet.…”
Section: Preparations and Properties Of Mxenesmentioning
confidence: 99%